2002
DOI: 10.1074/jbc.m206916200
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Catalytic Mechanism of Pseudomonas aeruginosa Exotoxin A

Abstract: The molecular nature of the protein-protein interactions between the catalytic domain from Pseudomonas aeruginosa exotoxin A (PE24H) and its protein substrate, eukaryotic elongation factor-2 (eEF-2) were probed using a fluorescence resonance energy transfer method. Single cysteine mutant proteins of PE24H were prepared and site-specifically labeled with the donor fluorophore IAEDANS (5-(2-iodoacetylaminoethylamino)-1-napthalenesulfonic acid), whereas eEF-2 was labeled with the acceptor fluorophore fluorescein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…The tip of domain IV with the diphthamide and the nucleotide-binding site in domain I are separated by 60 -70 Å depending on the conformation of eEF2. Furthermore, ADP-ribosylation does not induce any significant change in domain IV, which might be transmitted to domain I through domains III or V. This agrees with previous data that suggested that the binding of guanyl nucleotides does not affect the binding of eEF2 to ETA (37).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The tip of domain IV with the diphthamide and the nucleotide-binding site in domain I are separated by 60 -70 Å depending on the conformation of eEF2. Furthermore, ADP-ribosylation does not induce any significant change in domain IV, which might be transmitted to domain I through domains III or V. This agrees with previous data that suggested that the binding of guanyl nucleotides does not affect the binding of eEF2 to ETA (37).…”
Section: Discussionsupporting
confidence: 81%
“…The catalytic fragment of ETA with a C-terminal His 6 tag (PE24H) was overexpressed and purified as described (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional differences in the extracellular proteome were noted with respect to exotoxin A. Production of exotoxin A inhibits eukaryotic host cell protein synthesis by interacting with elongation factor-2, resulting in cell death [65]. While exotoxin A was detected in the supernatants of P. aeruginosa PAO1, its presence was limited to biofilms (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the crystal structure of the binary complex (enzyme and tetrasaccharide substrate) of A1‐III has been characterized . By examining the high‐resolution crystal structure of the binary complex, 3D model of AlgL and our experimental data, we can propose a reaction mechanism for AlgL . At present, the “Asn‐His‐Tyr catalytic triad” is considered to be important in polysaccharide lyases catalysis.…”
Section: Resultsmentioning
confidence: 97%